RP5-833A20.1/miR-382-5p/NFIA–Dependent Signal Transduction Pathway Contributes to the Regulation of Cholesterol Homeostasis and Inflammatory Reaction. Issue 1 (January 2015) - Hu, Yan-Wei; Zhao, Jia-Yi; Li, Shu-Fen; Huang, Jin-Lan; Qiu, Yu-Rong; Ma, Xin; Wu, Shao-Guo; Chen, Zhi-Ping; Hu, Ya-Rong; Yang, Jun-Yao; Wang, Yan-Chao; Gao, Ji-Juan; et al.
<x xml:space="preserve">Abstract</x> Objective— Cardiovascular disease caused by atherosclerosis is the number one cause of death in Western countries and threatens to become the major cause of morbidity and mortality worldwide. Long noncoding RNAs are emerging as new players in gene regulation, but how long noncoding RNAs operate in the development of atherosclerosis remains unclear. Approach and Results— Using microarray analysis, we found that long noncoding RNA RP5-833A20.1 expression was upregulated, whereas nuclear factor IA (NFIA) expression was downregulated in human acute monocytic leukemia macrophage–derived foam cells. Moreover, we showed that long noncoding RNA RP5-833A20.1 may decreases NFIA expression by inducing hsa-miR-382-5p expression in vitro. We found that the RP5-833A20.1/hsa-miR-382-5p/NFIA pathway is essential to the regulation of cholesterol homeostasis and inflammatory responses in human acute monocytic leukemia macrophages. Lentivirus-mediated NFIA overexpression increased high-density lipoprotein cholesterol circulation, reduced low-density lipoprotein cholesterol, and very-low-density lipoprotein cholesterol circulation, decreased circulation of inflammatory cytokines, including interleukin-1β, interleukin-6, tumor necrosis factor-α, and C-reactive protein, enhanced reverse cholesterol transport, and promoted regression of atherosclerosis in apolipoprotein E–deficient mice. Conclusions— Our findings indicated that the RP5-833A20.1/miR-382-5p/NFIA pathway was essential to the regulation of cholesterol homeostasis and inflammatory reactions and suggested that NFIA may represent a therapeutic target to ameliorate cardiovascular disease.